EKSPLORASI STRATEGI KOGNITIF SISWA SMA DALAM BERPIKIR GEOMETRI PADA FUNGSI INVERS - Laurin Wijayanti Khoiriyah; Fiki Alghadari; Bella Arisha (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
Mathematics learning is expected to develop students' geometric thinking skills and cognitive strategies, but in fact, these skills are still relatively low, especially in the material of functions. This study aims to analyze students' cognitive strategies in solving inverse function problems in terms of the Van Hiele geometric thinking level. This study uses a qualitative approach with a descriptive research type. The subjects of the study consisted of eleventh grade students selected based on Van Hiele's thinking levels from level 0 to level 3. Data were collected through tests, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study show that students' cognitive strategies differ at each Van Hiele thinking level. Students at the low level tend to use simple procedures and are not yet able to explain concepts in depth, while students at the high level are able to use systematic strategies, analyze conceptual relationships, and provide logical reasons for solving inverse function problems. Differences in geometric thinking abilities also affect students' cognitive strategies in solving problems. Therefore, learning is needed that can train students to think gradually so that geometric thinking abilities develop more optimally